Randomized controlled Phase III trial to evaluate omentum preserving gastrectomy for patients with advanced gastric cancer (JCOG1711, ROAD-GC). (8th July 2020) - Sato, Yuya; Yamada, Takanobu; Yoshikawa, Takaki; Machida, Ryunosuke; Mizusawa, Junki; Katayama, Hiroshi; Tokunaga, Masanori; Boku, Narikazu; Terashima, Masanori; ,
Abstract: Gastrectomy with omentectomy and D2 lymph node dissection is the current standard procedure for locally advanced gastric cancer. However, some retrospective studies have reported that omentectomy increased post-operative abdominal complications but provided no survival advantage over omentum preservation. Therefore, we plan a randomized controlled phase III trial to confirm the non-inferiority of omentum preservation compared with omentectomy in patients with cT3 (SS) or cT4a (SE) gastric cancer. A total of 1050 patients will be enrolled from 62 institutions over a period of 6.5 years. The primary end point is relapse-free survival, and the secondary end points are overall survival, blood loss, operation time and adverse events. This trial has been registered at the UMIN Clinical Trials Registry as UMIN000036253. Abstract : We designed a randomized controlled Phase III trial to confirm non-inferiority of omentum preservation compared with omentectomy in relapse-free survival for patients with cT3 (SS) or cT4a (SE) gastric cancer.